Editor’s Postscript for NANO Special Issue 15: Twin Peaks: The Return, Walter Benjamin, and Jeffrey Epstein - Matthew Lau (New York City College of Technology, 2020)
Matthew Lau's "Editor's Postscript for NANO Special Issue 15: Twin Peaks: The Return, Walter Benjamin, and Jeffrey Epstein," reveals that it will be Twin Peak’s critique of the power elite, especially their sexual exploitation of the young, along with other newly prescient aspects of the show referring to the horrifying moral rot at the heart of this late stage of capitalism, that will add the most combustible new fuel to its enigmatic fire, the expanding funeral pyre of Laura Palmer, the lost American girl next door.